2016
DOI: 10.1103/physrevb.94.115124
|View full text |Cite
|
Sign up to set email alerts
|

Interaction-driven topological superconductivity in one dimension

Abstract: We study one-dimensional topological superconductivity in the presence of time-reversal symmetry. This phase is characterized by having a bulk gap, while supporting a Kramers' pair of zero-energy Majorana bound states at each of its ends. We present a general simple model which is driven into this topological phase in the presence of repulsive electron-electron interactions. We further propose two experimental setups and show that they realize this model at low energies. The first setup is a narrow two-dimensi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 79 publications
(136 reference statements)
0
51
0
Order By: Relevance
“…It was also shown in Ref. [50] that z k is always a positive semidefinite matrix, and by extension it is straightforward to show that 0 k is also always positive semidefinite. Consequently, it is only possible for the DIII topological invariant to take a nontrivial value if both z k and 0 k are nonzero, as the anomalous self-energy is not restricted to be either positive or negative semidefinite in this case.…”
mentioning
confidence: 66%
See 3 more Smart Citations
“…It was also shown in Ref. [50] that z k is always a positive semidefinite matrix, and by extension it is straightforward to show that 0 k is also always positive semidefinite. Consequently, it is only possible for the DIII topological invariant to take a nontrivial value if both z k and 0 k are nonzero, as the anomalous self-energy is not restricted to be either positive or negative semidefinite in this case.…”
mentioning
confidence: 66%
“…It has also been proposed to realize class DIII topological superconductivity in a system of two Rashba nanowires [43][44][45] or two topological insulators [46] coupled to a single conventional superconductor, but repulsive interactions are also necessary to reach the topological phase in these setups, which require a strength of induced crossed Andreev (interwire) pairing exceeding that of the direct (intrawire) pairing [47][48][49]. While it would be beneficial to engineer a DIII topological superconductor in a noninteracting 1D system coupled to a single conventional superconductor, as such a setup could avoid relying on unconventional superconductivity or interactions that are difficult to control experimentally, it has been shown that this is not possible in a fully time-reversal invariant system [38,50].In this paper, we show that such a 1D topological superconductor in class DIII can be realized when time-reversal …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…More importantly, d-wave superconductors can induce an extended s-wave superconductivity, and this can be the main ingredient for the production of TRI MDs 29,32 . On the other way around, Majorana quasiparticles on the wire may couple to the nodal fermions in d-wave superconductors, and leaking of Majorana states in the substrate has been theoretically predicted 33 .…”
Section: Introductionmentioning
confidence: 99%